Image of Dunedin as a tourist destination: content analysis of tourism promotional websites - Abdul Razak, Norhanim (Global Academic Excellence, 2019)
Image plays a meaningful role in boosting the competitive edge of a particular tourist destination. As digital media have been receiving considerable importance in supplying information and act as marketing means in tourism, this study aims to explore the image of a tourist destination depicted in the websites by national and local promotional organisations. In investigating the destination image topic, this research explores the image of Dunedin as projected by tourism websites of the official bodies in the promotion of this city. A content analysis technique has been adopted in the assessment of these travel promotional websites. Overall, a very positive image of the city has been projected by both national and local organisations. Findings of this paper revealed that the national tourism organisation highlighted the Scottish origin of Dunedin and labelled the city as the Edinburgh of New Zealand. The primary asset or the unique selling proposition of the city as projected by both organisations is its rare wildlife particularly the penguins. Natural resources such as beaches and other wildlife especially the royal albatross, seals and sea lions and cultural heritage attributes like Larnach Castle, Dunedin Railway Station and Toitu Otago Settlers Museum formed the image of Dunedin as a tourist destination and this observation is reflected in both websites. Compared to the national tourism organisation, the local tourism authority presented more diverse attractions and sites including remote areas and hidden parts of the city. Its local knowledge of the city is further accentuated through the words such as hidden and insiders. In short, both unique features and familiar attributes are presented on the websites in portraying Dunedin as a fascinating and friendly tourist destination.